AN ANALYSIS OF FLOUTING COOPERATIVE PRINCIPLE OF THE CLASSROOM INTERACTION RECORDED IN VIDEO BETWEEN TEACHER AND STUDENTS - Ega Diestyah; Aan Erlyana Fardhani; I Putu Sukmaantara (EFL Education Journal, 2023)
This study investigates the classroom interaction between a teacher and students, focusing on the application of Paul Grice's Cooperative Principle theory. The objective is to identify instances of flouting maxim, including the maxim of quantity, quality, manner, and relation. Through a descriptive qualitative design, the research examines the data to gain insights into the occurrence and implications of flouting maxim in the classroom. The findings reveal eleven instances of flouting maxim across all four types. The study emphasizes the importance of English teachers' awareness of the Cooperative Principle as a guiding framework for English language instruction. By using authentic materials such as movies or advertisements, teachers can elucidate the hidden meanings behind utterances and enhance students' comprehension. This research contributes to improving classroom communication and fostering a deeper understanding of language use.